Luis F. Leloir - Houssay, Bernardo Alberto (1966)
This year Dr. Luis Federico Leloir reaches lhis sixtieth birthday. Born in a family whose members, apart from a few lawyers, were traditionally dedicated to large farming activities, he was the first to be interested in Science. After completing his medical studies and internship in 1932, he worked intensively in the Institute of Physiology of the Buenos Aires University Medical School, on a thesis about the role of the adrenals in carbohydrate metabolism. This was the prize for the best thesis of that year (1934).